Pelatihan Implementasi Penelitian Tindakan Kelas Bagi Guru melalui Webinar - Heru; Refi Elfira Yuliani; Rieno Septra Nery; Muslimin; Nurhayati (Jurnal Pengabdian Pada Masyarakat, 2022)
CLASSROOM ACTİON RESEARCH IMPLEMENTATİON TRAİNİNG FOR TEACHERS VİA WEBİNAR. PROFESSİONAL TEACHERS ARE the hope for every person who dedicates himself to being an educator at the Kindergarten to High School level. One of the demands in the continuous professional development of teachers is the implementation of scientific publications or innovative works. This community service aims to train teachers on Classroom Action Research and Article Writing in National Journals through webinars. Ninety-four participants participated in the training. Based on the results of the training, it was obtained that the participant's assessment of the quality of the training included: 1) the quality of the audio (voice) was very clear and clear at 93.83%; 2) visual quality (text, images) is very clear and clear by 92.34%; 3) the suitability of the material presented by the resource persons according to the title of the webinar by 94, 89%; 4) the quality of the material delivered by the resource persons is very good and easy to understand by 93.83%; 5) the question and answer session/discussion on the webinar was effective and was able to answer my questions by 90.43%. In addition, the participants wanted the PkM Team to provide further training in the form of 1) assistance in writing scientific articles; 2) development of interactive learning multimedia using Ms Power point; 3) handwriting learning video development; 4) development of LKPD; and, 5) development of TPACK-oriented RPP.